The Role of Physical Activity and Discipline in Character Formation (Literature Review Sport Education) - Reni Silviah (Siber Nusantara Review, 2024)
Literature Review The Role of Physical Activity and Discipline in Character Formation is a scientific article with the aim of analyzing whether physical activity and discipline play a role in character formation. A method that examines various research, articles and books that are relevant to the topic discussed. The results of this article are: 1) Physical activity plays a role in character formation, 2) Discipline plays a role in character formation. Apart from these 2 exogenous variables which influence the endogenous variable Job Satisfaction, there are many other factors, including health, achievement and physical condition.